8 Glugacon-like petide 1 loading during percutaneous coronary intervention (GOLD PCI) trial. (25th January 2018) - Giblett, JP; Clarke, SJ; McCormick, LM; Braganza, D; Densem, CG; O'Sullivan, M; West, NEJ; Villar, S; Hoole, SP
Abstract : Introduction: Glucagon-like peptide 1 (7–36) amide (GLP-1) is an incretin hormone, shown to protect against non-lethal cardiac ischemia-reperfusion injury. We investigated whether GLP-1 protected against PCI-induced myocardial infarction (PMI), attenuating cardiac troponin I (cTnI) release after elective PCI. Methods: A double-blind, randomised, placebo-control trial, conducted in a single UK centre, administered an iv infusion of GLP-1 (1.2 pmol/Kg/min) or saline to patients approximately 30 min before elective PCI. The primary endpoint was PMI defined as a cTnI elevation >5 xURL at 6 hours post-PCI. Secondary endpoints include TIMI flow and blush grade after PCI, rise in cTnI elevation and creatinine at 6 hours post-PCI and major adverse cardiovascular and cerebrovascular events (MACCE) at 6 months. Results: Of the 192 patients randomised (figure 1), 152 (79%) were male. Patient demographics were similar between the groups. There was no inter-group difference in the incidence of PMI: GLP-1 9 (9.8%) vs saline 8 (8.3%), p=0.28. Median cTnI elevation between the groups was also similar: GLP-1 20 [0–88.5] vs saline 10 [0–58.5] ng/L, p=0.28. Change in creatinine was no different between the groups (GLP-1–2.78±9.04 vs saline −1.75±8.74 μmol/L, p=0.73). Conclusion: GLP-1 did not confer cardioprotection against PMI after elective PCI, although the incidence of PMI in contemporary PCI is low.